MINORITY STATUS AND MIGRATION AS CORRELATES OF HEALTH AND WELL-BEING. (11th November 2018) - Glicksman, A; Ring, L; Kleban, M H
Abstract: The effects of immigration (including migration from culturally distinct US territories) on older adults in the US are often studied outside the larger context of minority aging, even though an overwhelming proportion of migrants qualify as "minority". This presentation asks the question: Does migration status have an effect on the health and wellbeing of these elders, or does their minority status in American society alone account for any differences in outcome from the majority population? Utilizing both census data and the results from a local omnibus health survey, this study compared outcomes of three groups of older adults living in Philadelphia- Puerto Ricans born in the continental US, migrant Puerto Ricans, and white, non-Hispanics. The Puerto Rican born population differed from both the non-minority and locally born Puerto Rican groups on measures of mental and physical health, poverty, and service access, clearly demonstrating migration's impact as independent of minority status.